The Tanzania Second Social Action Fund (TASAF II) : Knowledge Sharing and Learning for Better Delivery of Results - Ida , Manjalo (World Bank, Washington, DC, 2012)
This report is currently implementing the second phase of the Tanzania Social Action Fund, known as TASAF II. The main objective of TASAF II is to empower communities to access opportunities so that they can request, implement, and monitor sub-projects that contribute to improved livelihoods that are linked to indicator targets of the Millennium Development Goals (MDGs) as stipulated in the National Strategy for Growth and Reduction of Poverty, popularly known by its Kiswahili acronym MKUKUTA. One major challenge of delivering TASAF II is its expanded mandate and full mainstreaming into local government authorities (LGA) operations. LGAs had to be provided with the opportunity to internalize an objective assessment achievements and challenges observed during the implementation of TASAF I, through the sub-project cycle. This would provide opportunity for the joining LGAs to learn from the experiences of TASAF I, thus create space and environment for efficient and cost-effective delivery of TASAF II.